2021
DOI: 10.1001/jamanetworkopen.2021.33935
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Infection Associated With Administration of Intravenous Iron

Abstract: IMPORTANCEIntravenous iron is recommended by many clinical guidelines based largely on its effectiveness in reducing anemia. However, the association with important safety outcomes, such as infection, remains uncertain. OBJECTIVE To examine the risk of infection associated with intravenous iron compared with oral iron or no iron. DATA SOURCES Medline, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for randomized clinical trials (RCTs) from 1966 to January 31, 2021. Ongoing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 237 publications
(1,393 reference statements)
1
38
1
Order By: Relevance
“… 17 A meta-analysis of studies across a broad range of conditions found that intravenous iron was associated with an increased risk of infection (rate ratio (RR) 1.17; 95% CI 1.04 to 1.31). 8 This was not confirmed across heart failure studies. Most studies did not define infection a priori, and the authors note potential bias.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“… 17 A meta-analysis of studies across a broad range of conditions found that intravenous iron was associated with an increased risk of infection (rate ratio (RR) 1.17; 95% CI 1.04 to 1.31). 8 This was not confirmed across heart failure studies. Most studies did not define infection a priori, and the authors note potential bias.…”
Section: Discussionmentioning
confidence: 92%
“…Labile (free) iron can result in the generation of reactive oxygen species, which could lead onto oxidative stress and cell damage 17. A meta-analysis of studies across a broad range of conditions found that intravenous iron was associated with an increased risk of infection (rate ratio (RR) 1.17; 95% CI 1.04 to 1.31) 8. This was not confirmed across heart failure studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Original Investigation titled “Risk of Infection Associated With Administration of Intravenous Iron: A Systematic Review and Meta-analysis,” 1 published November 12, 2021, the number of participants and the number of infection events in each group were incorrectly recorded. Once corrected, the overall point estimate for the risk of infection changed from a relative risk of 1.17 (95% CI, 1.04-1.13, I 2 = 37%) to 1.16 (95% CI, 1.03-1.29, I 2 = 36%).…”
mentioning
confidence: 99%